2000
DOI: 10.2527/2000.7851125x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gilt development diet on the reproductive performance of primiparous sows.

Abstract: The objective of this study was to evaluate the effect of development diet on first-parity reproductive performance across different genetic types of females. Gilts (n = 708) 8 to 15 d of age from five genetic lines were assembled using a segregated early weaning protocol. Genetic types represented industry variation for reproductive capacity and lean growth potential. Sampling procedures were not designed to evaluate performance differences among the genetic lines. When the gilts weighed approximately 20 kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In agreement, Johnson et al (2009) and Klindt et al (2001) reported no differences (Po0.05) between gilts reared ad libitum or restricted for STAY or litter size. Stalder et al (1998) reported higher STAY, but not litter size, for gilts fed restrictively vs. ad libitum from 120 to 180 d of age. Newton and Mahan (1993) reported gilts fed ad libitum vs. 60% of ad libitum from 150 to 240 d of age had a similar number of pigs born alive but an increased pre-weaning mortality.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In agreement, Johnson et al (2009) and Klindt et al (2001) reported no differences (Po0.05) between gilts reared ad libitum or restricted for STAY or litter size. Stalder et al (1998) reported higher STAY, but not litter size, for gilts fed restrictively vs. ad libitum from 120 to 180 d of age. Newton and Mahan (1993) reported gilts fed ad libitum vs. 60% of ad libitum from 150 to 240 d of age had a similar number of pigs born alive but an increased pre-weaning mortality.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have quantified the relationship between gilt body weight and body composition, achieved through dietary manipulation, on subsequent reproductive performance (Barczewski et al, 1990;Johnson et al, 2009;Klindt et al, 2001;Newton and Mahan, 1993;Stalder et al, 1998). However, few studies have examined estrous traits in relation to subsequent reproductive performance (Cronin et al, 1982;Gäde et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…A number of studies have placed importance on the relationship between body composition of gilts during development and subsequent reproductive performance (O'Dowd et al, 1997;Cia et al, 1998;Stalder et al, 2000). Particular emphasis has been given to body fat 1926 as a percentage of BW was increased at mating (26.0 vs. 21.9%, P = 0.005).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the plus feed treatment, which is similar to the higher dietary energy level during mid-gestation in our study, resulted in an average of 2 more piglets without decreasing the average piglet birth weight. Stalder et al (2000) found no influence of gilt development diet on first parity maternal performance, but found that genetic line  development diet interaction was a significant source of variation for litter size and litter weight at birth. Although gilt development strategy may influence the reproductive performance of gilts, the results from the present study suggest that most of the gilts, regardless of dietary treatment during rearing and mid-gestation, were in adequate body condition at parturition resulting in similar numbers of piglets born alive and litter birth weights.…”
Section: Discussionmentioning
confidence: 90%